O contato com a natureza e o desenvolvimento sensório-motor de crianças da educação infantil - Pomatti, Daniela (2020)
The main objective of this article is to discuss and understand the benefits arising from the child's relationship with nature, which benefit his development. The character of this research is exclusive of bibliographic nature, based on the use of publications of theses, dissertations and books. After conducting the studies, it was possible to understand that nature has a fundamental role in the development of children. Through contact with her, children develop more actively, explore physical challenges, which benefit motor coordination, strengthen creativity and stimulate imagination, for these reasons it is necessary for school institutions to include activities to be carried out in their daily lives. amidst nature, thus making it an educational space.